ENTERPRISE SUSTAINABILITY MAINTENANCE UNDER INNOVATION DEVELOPMENT - Karina A. BARMUTA (Advanced Engineering Research)
The concept of sustainable development and its factors, innovation activity role in the enterprise development are considered. Necessity of the control system development for the sustainability support is proved. It is considered a guarantee of the enterprises survival under the market system of management.